Traumatic Brain Injury due to Bear maul: A Case report - Jha, Prabhat; Khadka, Nilam Kumar (Nepal Journal of Neuroscience, 2024)
Introduction: Interaction between bears and human is a common occurrence in hilly region of Nepal. Interactions usually occur where humans live close to the bears’ habitat. In hilly regions of Nepal, it can occur when humans go to the jungle for cattle grazing or collecting fodder. The injuries most commonly occur in facial region. Traumatic brain injury due to bear maul can also occur.Case Report: This case report describes a 19 year female who sustained traumatic brain injury due to bear maul.Discussion: Management of traumatic brain injury due to bear maul is usually straight forward with goals directed towards aggressive lavage, debridement and infection control. Rabies and tetanus prophylaxis should be given to all patients along with anti tetanus and anti rabies immunoglobulin.